Uso do sequenciamento de alto desempenho para caracterizar comunidades microbianas envolvidas na produção de metano e coprodutos a partir da digestão anaeróbia da vinhaça - Iltchenco, Janaína (My University, 2017)
Vinasse is a residue resulting from the production of ethanol generated in large quantities in Brazil, and can be approved for biogas production. Several microorganisms act in the degradation of the vinasse to obtain biogas, and the study of microbial consortia is essential for optimization of the process. This work aimed to evaluate the production of methane and co-products from the vinasse, as well as to identify bacteria and archaea involved in the production of methane by high performance sequencing. Initially, the potential of enrichment of the inoculum in biogas production was verified. The methane production was evaluated with Zinder medium and Monteggia medium with and without acetate, and later it has tests with previous environment of the inoculum coming from the treatment plant of vegetable oil and vinasse. Concomitant experiments were carried out in a 5L reactor, with different samples (0,25; 0,5; 0,75; 1,0 ; 1,25; 1,5 and 1,7), in which gas samples were collected and liquid for analysis of methane production, volatile fatty acids, removal of COD and identification of microorganisms. It was found to be an addition of acetate to the nutrient media yielding the production of 5.9 mmol / CH 4 with Zinder medium. The bioassay without enrichment was highlighted according to the ratio S0/X0 = 1,5 which produced 12,48 mmol/CH4. In all bioassays, acetic, propionic and valeric acids were produced, and the highest acid production in relation to S0/X0=1,7 was obtained with enrichment in the inoculum environment, where 115mg.L -1 acetic acid, 195 mg.L1 of propionic acid and 154 mg.L -1 of butyric acid. A microbiota of the S0/X0=1.5 ratio showed a predominance of bacteria of the phyla Bacteroidetes (49.92%), Firmicutes (12,02%) and Proteobacteria (11,23%). The genera Bacteroides, OTU belonging to the Porphyromonadaceae Family; and archaea Methanobacterium, Methanosaeta and Methanosarcina were the predominant. Bacteroidetes (22,63%), Euryarchaeota (19,94%), and Firmicutes (16.33%) were the most important ones, with a larger scale (5L), a microbiota evaluated according to S0/X0 = 1,7; genus Methanosaeta (15%), microorganism of the family Porphyromonadaceae (13,54%) and Candidatus Cloacamonas, (9,36%) in the sample of the peak of production. As archaea found in the samples were: Methanobacterium sp., Methanomas sp., Methanosaeta sp., Methanomassiliicoccus sp, and microorganisms of the order Methanobacteriales. A vinasse showed great potential for methane production, and a wide diversity of microorganisms identified that help in the understanding and optimization of the process.
A vinhaça é um resíduo resultante da produção de etanol gerada em grande quantidade no Brasil, e pode ser aproveitada para produção de biogás. Diversos microrganismos atuam na degradação da vinhaça para obtenção de biogás, e o estudo desses consórcios microbianos é imprescindível para que haja otimização desse processo. Esse trabalho teve como objetivo avaliar a produção de metano e coprodutos a partir da vinhaça, bem como identificar bactérias e arqueas envolvidas na produção de metano por sequenciamento de alto desempenho. Inicialmente, verificou-se a potencialidade de enriquecimento do inóculo na produção de biogás. A produção de metano foi avaliada com meio Zinder e Meio Monteggia com e sem acetato, e posteriormente foram feitos testes com prévia ambientação do inóculo proveniente de estação de tratamento de óleo vegetal e vinhaça. Concomitante, foram feitos experimentos em reator de 5L, com diferentes (0,25; 0,5; 0,75; 1,0; 1,25; 1,5; e 1,7), nas quais foram coletadas amostras de gás e líquidas para análises de produção de metano, ácidos graxos voláteis, remoção de DQO e identificação de microrganismos. Verificou-se que a adição de acetato aos meios nutritivos proporcionou a produção de 5,9 mmol/CH4 com meio Zinder. O bioensaio sem enriquecimento destacou-se conforme relação S0/X0=1,5 que produziu 12,48 mmol de CH4. Em todos os bioensaios houve produção de ácido acético, propiônico e valérico, e a maior produção de ácidos ocorreu na relação S0/X0=1,7 com enriquecimento na ambientação do inóculo, onde foi produzido 115mg.L -1 de ácido acético, 195 mg.L -1 de ácido propiônico e 154 mg.L -1 de ácido butírico. A microbiota da relação S0/X0=1,5 mostrou a predominância de bactérias dos filos Bacteroidetes (49,92%), Firmicutes (12,02%) e Proteobacteria (11,23%). Os gêneros Bacteroides, OTU pertencente à Família Porphyromonadaceae; e arqueas Methanobacterium, Methanosaeta e Methanosarcina foram os predominantes. No experimento em maior escala (5L), a microbiota foi avaliada conforme relação S0/X0=1,7, destacando-se filos Bacteroidetes (22,63%), Euryarchaeota (19,94%) e Firmicutes (16,33%); gênero Methanosaeta (15%), microrganismo da familia Porphyromonadaceae (13,54%) e Candidatus Cloacamonas, (9,36%) na amostra do pico de produção. As arqueas encontradas nas amostras foram: Methanobacterium sp., Methanomas sp., Methanosaeta sp., Methanomassiliicoccus sp, e microrganismos da ordem Methanobacteriales. A vinhaça mostrou um grande potencial para produção de metano, e uma vasta diversidade microrganismos identificados que auxiliam no entendimento e otimização do processo.
Keywords: Vinhaça; Biogás; Metano; Álcool; Microorganismos; Vinasse; Methane; Biogas; Alcohol; Microorganisms